The Influence of Sunnah Prayer Spirituality on the Quality of Education - Hambali , Muh.; Wangi, Dewita Sekar (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This study focuses on the influence of spirituality on the quality of education at MAN 3 Kediri. The purpose of the study was to test the extent to which spirituality carried out every morning can improve the quality of student learning outcomes. Spirituality activities in the form of dhuha prayer can affect the quality of learning concentration. The quality of education is characterized by the quality of student learning concentration. The approach used is quantitative with a descriptive research type. The data collection instrument is in the form of a Likert-scale questionnaire. The study population consisted of 401 class XI students of MAN 3 Kediri, with a sample of 80 students selected using simple random sampling techniques and the Slovin formula. Data assistance was analyzed using a simple linear regression test with the SPSS 24 application. The results showed that spirituality in the form of the habit of dhuha prayer has a positive influence on the quality of education in MAN 3 Kediri students. The calculated F value is 58.274 with a significance level of 0.000 <0.05, and a simple regression equation is obtained Y = 12.98 + 0.751X. Spirituality sharpened in dhuha prayer contributes 42.8% to the quality of learning in its concentration, which is categorized as a moderate influence. Meanwhile, other factors outside the scope of this study contributed 57.2%. This shows that the spirituality of sunnah prayer in the form of dhuha prayer helps students to be more focused or concentrated in learning, calmer in learning and can understand the lesson better